Análisis físico-químico de la calidad del agua en el canal El Macho de la ciudad de Machala - López Apolo, Miguel J. (2015)
The current research work was done in Machala city, in the El Oro province, within the Objectives based upon the physycal-chemical analysis of water quality in the Macho canal, where points of sampling were established during its lifetime alongside the canal respective codes, in the beginning receiving water sampling from banana spots.